This is just a field trip, right? Enhancing STEM Engagement and Content Knowledge through Experiential Learning for HBCU Students in Texas - King Miller, Beverly; Burnett, Camille; Jones, Marilyn (Experiential Learning and Teaching in Higher Education, 2025)
This study investigates the impact of a STEM field trip on engagement in STEM learning and interest in STEM among students at a Historically Black College and University (HBCU) in Texas. Using Kolb’s (1984) experiential learning model as a theoretical framework, the research explores how engaging, hands-on activities during the field trip enhance students' content knowledge and interest in STEM. Data were collected from six students and two faculty members who participated in the field trip and completed pre- and post-trip questionnaires. The findings indicate that field trips are valuable for increasing content knowledge, fostering student engagement, and promoting interdisciplinary collaboration. Although the study's sample size was limited, the positive outcomes suggest that incorporating more field trips could benefit HBCU students, especially those pursuing careers in STEM education. The study underscores the need for collaborative efforts among different academic departments to support experiential learning and enhance the recruitment and preparation of STEM teachers, ultimately contributing to a more diverse STEM workforce. Future research will aim to include a larger participant pool and secure increased faculty and administrative support to validate these findings.